Data Integrity and Client Side Data Security Trust Model in Cloud: Ensuring Data Integrity and Client Side Security in Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Cloud computing demands multifaceted security solutions for a big, loosely linked system. Incloud computing, applications databases are housed in remote data centers, where the reliability of data service management is uncertain. Customers' confidence in a cloud service provider's reliability andsecurity is a key factor in their decision to use that provider for mission-critical data. We describe thethreats, vulnerabilities, risks associated with cloud computing, and we present a cloud computingsecurity development lifecycle model to ensure user safety and facilitate maximum data protection whilestill reaping the benefits of cloud computing. To prevent unwanted access, alteration, or deletion of bothstatic dynamic data, an algorithm for validating their integrity is presented.